2022
DOI: 10.1177/03000605221129543
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 induces gastrointestinal symptoms and affects patients’ prognosis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection caused the pandemic of coronavirus disease 2019 (COVID-19). Gastrointestinal (GI) involvement is common among patients with COVID-19, and GI symptoms can appear earlier than respiratory symptoms. Except for direct infectious effects, patients infected with SARS-CoV-2 are at risk of complications requiring gastroenterological management. Diarrhea is the most common GI symptom in patients with COVID-19 and occurs in up to half of them. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Notably, recent clinical studies have reported that an increasing proportion of COVID-19 patients develop gastrointestinal symptoms ( Chen et al, 2020 ; Jin et al, 2020 ; Redd et al, 2020 ; Blackett et al, 2022 ; Freedberg and Chang, 2022 ; Jin et al, 2022 ) and direct evidence of active SARS-CoV-2 replication has been found in the intestines ( Qian et al, 2021 ; Zuo et al, 2021 ; Cuicchi et al, 2022 ). Intestinal infection can induce the infiltration of plasma cells and lymphocytes in the intestinal mucosa of COVID-19 patients ( Xiao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, recent clinical studies have reported that an increasing proportion of COVID-19 patients develop gastrointestinal symptoms ( Chen et al, 2020 ; Jin et al, 2020 ; Redd et al, 2020 ; Blackett et al, 2022 ; Freedberg and Chang, 2022 ; Jin et al, 2022 ) and direct evidence of active SARS-CoV-2 replication has been found in the intestines ( Qian et al, 2021 ; Zuo et al, 2021 ; Cuicchi et al, 2022 ). Intestinal infection can induce the infiltration of plasma cells and lymphocytes in the intestinal mucosa of COVID-19 patients ( Xiao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on clinical symptoms in the respiratory tract, as viral infection can cause acute respiratory distress syndrome and respiratory failure, which are considered the main causes of death in COVID-19 patients ( Huang et al, 2020 ; Empson et al, 2022 ; Ramadori, 2022 ; Wang and Perlman, 2022 ). However, ACE2 is also highly expressed in the human intestinal tract, and a increasing number of patients presented with gastrointestinal symptoms ( Liang et al, 2020 ; Lin et al, 2020 ; Nobel et al, 2020 ; Muus et al, 2021 ; Blackett et al, 2022 ; Freedberg and Chang, 2022 ; Jin et al, 2022 ). Furthermore, direct evidence of active SARS-CoV-2 replication in the intestines has been found in clinical samples ( Xiao et al, 2020 ; Qian et al, 2021 ; Zuo et al, 2021 ; Cuicchi et al, 2022 ; Freedberg and Chang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence revealed that cardiovascular involvement and inflammation were highly associated with poor prognosis and mortality [ 54 58 ]. In addition, neurological symptoms, such as headache, fatigue, and loss of olfactory sensation, as well as gastrointestinal reactions, were common adverse prognostic events [ 59 , 60 ]. In the present study, we found that symptoms after quarantine were positively associated with prognosis, rather than initial symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should seek medical attention if their symptoms persist or worsen. Follow-up care is essential, and the resolution of the infection should be confirmed with repeated testing when necessary[ 113 ]. Please refer to Table 8 for a summary of the proposed treatments.…”
Section: Discussionmentioning
confidence: 99%